(untitled) (The Review of Diabetic Studies, 2025)
Seasonal viruses such as Influenza and Respiratory syncytial virus pose recurrent public health challenges, particularly in communities with limited health literacy and persistent misconceptions about transmission and prevention. This review explores the impact of medical staff deployed through structured awareness initiatives aligned with national health strategies on improving community literacy and preventive culture. Drawing on community education principles emphasized by the Saudi Vision 2030 transformation goals and community health promotion carried out in urban and rural settings, the review highlights clinicians’ roles beyond treatment—including counseling, public lectures, viral symptom literacy communication, and myth correction. Evidence indicates that trusted medical outreach enhances public understanding of viral transmission, increases engagement with hygiene behaviors and vaccination literacy, and helps bridge critical knowledge gaps. The review concludes that medical staff act as essential drivers of community viral literacy, shaping prevention culture through direct communication and tailored outreach, ultimately strengthening seasonal preparedness and fostering sustained public health awareness.